Clinicoradiological Correlation of Serum Procalcitonin Values in Degenerative Lumbar Disc Disease - Bele, Abhijeet; Acharya, Jigmisha; Singhal, Manoj; Panchariya, Piyush Kumar (Nepal Journal of Neuroscience, 2023)
Introduction: Low back pain (LBP) as a result of prolapsed intervertebral disc is one of the common causes of the morbidity and disability in current population. We assessed any association of inflammatory marker serum procalcitonin in degenerative disc disease. Materials & Methods: A prospective analytical study carried out at our tertiary care institute over one year from Dec 2021 to Dec 2022 after clearance from institute ethical committee. Total of 68 patients aged 18 to 65 years with low back pain with lumbar disc herniation on MRI imaging were included in the study. Serum procalcitonin levels were assessed using electrochemiluminescence technique on e411 Elecsys 2010. Results: The median values of serum procalcitonin were higher in early phase of disease tends to stabilising with chronicity of symptoms. There was a positive correlation between mean VAS scores and procalcitonin levels, those patients with higher procalcitonin values clinically had positive straight leg raising test and in the long run required more operative interventions. Conclusions: Lumbar degenerative disc disease has a strong inflammatory basis and serum values of procalcitonin can be useful objective marker to predict extent of inflammation with prediction of possible clinical course of disease.